Pediatric Myxedema Coma - presenting as Surgical Abdomen - G V Basavaraj; H S Vinayaka; Kiruthiga Sugumar (Wolters Kluwer Medknow Publications, 2018)
Myxedema com, also called myxedema crisis is a rare life threatening clinical condition that represents severe hypothyroidism. It may be the initial presentation in pediatric patients with prolonged untreated hypothyroidism. Myxedema coma should be suspected in pediatric patients with altered mental status, hypothermia and cardiovascular instability. This condition is fatal without treatment. Thyroid replacement should be initiated as early as possible. Early intervention in hypothyroid patients and in patients where hypothyroidism is suspected has shown to prevent morbidity and mortality associated with myxedema crisis.